Recycling buildings : renovations, remodelings, restorations, and reuses - Thompson, Elisabeth Kendall (New York : McGraw Hill Education, 1977)
For the investor with an adventurous spirit, with a concern for the quality and variety of the urban experience, with an eye for the scale and color of old buildings, and a sense of the human need for continuity from the past to present and on to the future, renovating, rehabilitating or restoring the old building for reuse can be a rewarding and satisfying experience. This is especially true of the old building put back into use as a lively part of the daily lives of people. That is, in essence, the reason for this book, and the examples shown in the pages not only illustrate what has been done but suggest, it is hoped, further equally imaginative ways of giving new life to old buildings.
Preface -- Renovation and remodeling for living -- Renovation and remodeling for business -- Renovation and remodeling for selling and shopping -- Renovation and remodeling for community use -- Rehabilitation and renovation for reuse -- Restoration and preservation of historic buildings -- Additions designed for neighborhood preservation -- Index.
Includes index.
Keywords: BUILDINGS -- REPAIR AND RECONSTRUCTION